Business Failure Prediction Model Using Accounting Anomalies Indices - Mahnani, Akram; Mohammadi, Ahmad; Moradi, Mahdi; Badavar Nahandi, Younes; Pourkarim, Yaghoub (Business, Marketing, and Finance Open, 2024)
The main purpose of this study was to identify and analyze the relationships between accounting anomalies and the prediction of the probability of business failure in companies listed on the Tehran Stock Exchange. Based on research methods and data collection, this study is quantitative, descriptive, analytical, and causal in nature. In terms of its objective, it is considered an applied research. The statistical population of this research included all companies listed on the Tehran Stock Exchange. A sample of 148 companies was randomly selected. In order to analyze the collected data, the t-test was used to test the significance of the regression model. The statistical software employed in this study was EViews. The results indicated that there is a significant relationship between business failure and accounting anomalies (p < 0.05). In other words, the observed difference in the mean business failure prediction between the groups is statistically significant. The mean difference between the two groups was -0.258, indicating that the average business failure prediction in one of the groups (most likely the “post-failure” group) is lower than in the other group. This difference may indicate a considerable reduction in the prediction of business failure.